Feline Coronavirus Antivirals: A Review - Manon Delaplace; Hélène Huet; Adèle Gambino; Sophie Le Poder (Pathogens, 2021)
Feline coronaviruses (FCoV) are common viral pathogens of cats. They usually induce asymptomatic infections but some FCoV strains, named Feline Infectious Peritonitis Viruses (FIPV) lead to a systematic fatal disease, the feline infectious peritonitis (FIP). While no treatments are approved as of yet, numerous studies have been explored with the hope to develop therapeutic compounds. In recent years, two novel molecules (GS-441524 and GC376) have raised hopes given the encouraging results, but some concerns about the use of these molecules persist, such as the fear of the emergence of viral escape mutants or the difficult tissue distribution of these antivirals in certain affected organs. This review will summarize current findings and leads in the development of antiviral therapy against FCoV both in vitro and in vivo, with the description of their mechanisms of action when known. It highlights the molecules, which could have a broader effect on different coronaviruses. In the context of the SARS-CoV-2 pandemic, the development of antivirals is an urgent need and FIP could be a valuable model to help this research area.